Examining the relationship between motivation levels and academic achievement in mathematics: A quantitative analysis of Kuzhugchen Middle Secondary School - Kencho; Shekhar Nath Mishra (Bhutan Journal of Research and Development, 2024)
Performance in mathematics has been declining over the years in Bhutan. There are many studies on motivation and mathematics. However, fewer papers are available in the Bhutanese context. Thus, of the many factors, this study investigated the impact of motivation on the academic performance of the students in the Kuzhugchen Middle Secondary School, Thimphu Dzongkhag (district). Out of 142 students, data were collected from 108 students (54 males and 54 females) selected using a proportionate random sampling. The t-test results revealed that there is a significant difference between academic performance and gender and no significant difference between motivation and gender. We also found a significantly small and positive correlation between the expectancy scale and academic performance, a moderate and negative correlation between the affect scale and academic performance, and no correlation between the value scale and academic performance. The findings of this study call for teachers, parents and other stakeholders to investigate the factors affecting mathematics performance and intervene accordingly. Furthermore, similar studies in other parts of the country, especially in rural areas, are recommended for new insights into motivation and academic performance.